2015
DOI: 10.3390/molecules20010595
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Cell Compatibility and Degradability of Collagen-Modified Poly(lactic acid)

Abstract: Poly(lactic acid) (PLA) was modified using collagen through a grafting method to improve its biocompatibility and degradability. The carboxylic group at the open end of PLA was transferred into the reactive acylchlorided group by a reaction with phosphorus pentachloride. Then, collagen-modified PLA (collagen-PLA) was prepared by the reaction between the reactive acylchlorided group and amino/hydroxyl groups on collagen. Subsequently, the structure of collagen-PLA was confirmed by Fourier transform infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
3
24
0
1
Order By: Relevance
“…These results are in good agreement with those of Cui et al, 77 who observed a significantly higher degree of degradation of PLA compared with a PLA blend that contains collagen. Incorporation of collagen and silver NPs into the blends' composition caused a slow degradation, probably because of the stabilizing effect of silver NPs.…”
Section: In Vitro Degradation Studysupporting
confidence: 92%
“…These results are in good agreement with those of Cui et al, 77 who observed a significantly higher degree of degradation of PLA compared with a PLA blend that contains collagen. Incorporation of collagen and silver NPs into the blends' composition caused a slow degradation, probably because of the stabilizing effect of silver NPs.…”
Section: In Vitro Degradation Studysupporting
confidence: 92%
“…The result as mentioned above corresponded well with all the basic chemical groups found along the backbone of PLA. For PTX, major vibrational modes included C-H out-of-plane or C-C=O deformation at 689 cm -1 , C-H in-plane deformation at 803~941 cm -1 , C-O stretching at 1049~1090 cm -1 , C-N stretching at 1274 cm -1 , CH 3 deformation at 1330~1380 cm -1 , C=C ring stretching at 1444 cm -1 , C-C stretching at 1579~1652 cm -1 , N-H bending at 1640 cm -1 , C=O stretching at 1720~1727 cm -1 , (C=O stretching) of amide group at 1733 cm -1 , CH3/C-H stretching at 2541~2973 cm -1 , -CH sp 3 stretching at 3066 cm -1 , N-H/O-H stretching at 3339 cm -1 , agreed with those peaks of pure paclitaxel as reported in the literature [4,6,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Those main and minor vibrational modes of plain PLA and pure paclitaxel were summarized in Table 2.…”
Section: Fourier-transform Infrared Spectroscopy (Ftir)supporting
confidence: 88%
“…Paclitaxel concentration in DMSO 2.5 mg/100 ml (50%), 5 mg/100 ml (100%) Table 2 Selected FTIR absorption peaks for PLA [14][15][16][17][18][19][20][21][22][23][24] and paclitaxel [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Experiment study for the electrospun paclitaxel mixed PLA nano bers on top of a thin lm of same compositions.…”
Section: Resultsmentioning
confidence: 99%